Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India - Basu, Srimoyee; Chandra, Kailash; Venkatesan, Thiruvengadam (Zootaxa, 2018)
Metrocoris sikkimensis sp. nov. is described from Sikkim, northeastern India, compared with similar species, included in an identification key and its geographical distribution is mapped. This species is assigned to the Metrocoris compar group based on the venter of the body entirely blackish and the male fore femur slender and unarmed. It can be distinguished from other species of the group based on the dark mesosternum without yellow markings, by the apically curved male paramere without setae, and by the structure of male endosomal sclerites.